Innovative technologies for the creation of low-calorie dairy products using plant components - O. Petrova; N. Shevchuk; A. Ziuzko; Y. Barkar (Тваринництво та технології харчових продуктів, 2025)
The development of low-calorie dairy products using plant-based ingredients is becoming increasingly relevant due to the growing demand for healthy eating and alternatives to traditional dairy products. The study background was based on the need to develop functional products with a reduced calorie load that combine high nutritional value with attractive organoleptic properties. The study aimed to develop low-calorie products based on plant-based raw materials using innovative technologies such as protein extraction, fermentation and ultrafiltration, ensuring a reduction in calories without losing texture, taste and shelf life. High-quality plantbased ingredients (soya, almonds, oats) and probiotic cultures were used, and the methodology included the isolation of protein isolates through extraction, further fermentation to improve flavour and enrich beneficial microorganisms, and ultrafiltration to help concentrate proteins, remove sugars and ensure product stability. The results showed that the developed products, namely fermented soya yoghurt (55 kcal/100 g), almond milk (30 kcal/100 ml) and oatmeal cream dessert (80 kcal/100 g), demonstrated a significant reduction in calories by 20-50% compared to traditional dairy analogues. All samples maintained a stable texture, homogeneity and high organoleptic characteristics for 7 days at +4°C, with an average score of 4.8 out of 5 according to the expert panel. Additionally, the study determined that the use of ultrafiltration ensured long-term product stability, while fermentation contributed to improved flavour characteristics and increased biological value. The study results confirmed the effectiveness of innovative technologies in creating competitive low-calorie products from plant components. The practical significance of the study is determined by possibility of implementing the results obtained in industrial production to meet the needs of the modern market focused on healthy eating